2019
DOI: 10.12927/hcpol.2019.25940
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Oral Health and Barriers to Seeking Care: Perspectives of Caregivers Seeking Paediatric Hospital Dental Treatment

Abstract: Objectives: To investigate the demographics of children (and their caregivers) requiring hospital-based tertiary dental care, oral health services use and perceptions of and barriers to oral healthcare in Nova Scotia. Method: A questionnaire was administered to caregivers ( N = 62) on behalf of their child ( N = 62). Results: Nearly half (45.8%, N = 27) of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, educational interventions in health care centers and oral health clinics should also be considered. Although the effectiveness of educational interventions in such settings to promote oral health has been examined in several studies [ 23 ], there is still a research gap regarding theory-based health education programs in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…However, educational interventions in health care centers and oral health clinics should also be considered. Although the effectiveness of educational interventions in such settings to promote oral health has been examined in several studies [ 23 ], there is still a research gap regarding theory-based health education programs in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has found that the majority of children entering OOHC do not access or receive referral for health assessments as recommended [ 27 ]. It has also been found that foster and kinship carers experience various challenges in seeking oral health care for the children in their care [ 28 , 29 ]. There can be foster agency problems such as having dental treatment pre-approved, or poor communication between foster care agencies and carers [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that foster and kinship carers experience various challenges in seeking oral health care for the children in their care [ 28 , 29 ]. There can be foster agency problems such as having dental treatment pre-approved, or poor communication between foster care agencies and carers [ 28 , 29 ]. Other systemic barriers include child transience, long waiting lists for the children to receive dental care due to reliance on the public health care system, and lack of dental professionals [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations